Molecular analysis of the rpsL gene for rapid detection of streptomycin-resistant Mycobacterium tuberculosis: a meta-analysis. (August 2014) - He, Jing; Zhu, Baosheng; Yang, Zhaojie; Hu, Binbin; Lin, Lianbing; Zhang, Qi
Abstract Background: Drug-resistant Mycobacterium tuberculosis (MTB) is a major threat to tuberculosis (TB) control programs and public health. Most conventional methods of drug susceptibility testing (DST) are precise but time-consuming. Molecular analysis of the rpsL gene has been used widely in diagnosing streptomycin-resistant MTB since it is rapid and specific. The aim of the present study was to perform a meta-analysis to assess the accuracy of molecular assay of the rpsL gene for the rapid detection of streptomycin-resistant MTB. Methods: We searched PubMed, Web of Science, and EBSCO databases for studies that applied a molecular assay of the rpsL gene to detect streptomycin-resistant MTB with a conventional method as the reference. The sensitivity and specificity were pooled by a random effect model using Meta-DiSc software. A summary receiver operating characteristic curve (SROC) was applied to summarize the diagnostic accuracy. Results: A total of 22 studies involving 2618 specimens with 1372 streptomycin-resistant and 1246 streptomycin-susceptible specimens met our inclusion criteria. The overall sensitivity and specificity estimates were 0.64 (95% confidence interval (CI) 0.61–0.66) and 1.00 (95% CI 0.99–1.00), respectively. The area under the SROC curve was 0.9069 and the Cochrane (Q*) index was 0.8387. Conclusions: This meta-analysis reveals that molecular assay of the rpsL gene is a reliable and useful method for the detection of streptomycin-resistant MTB.